Implementasi Program Pemerintah dalam Pembangunan Drainase Jalan Teuku Umar Tulungagung sebagai Upaya Pengendalian Banjir dan Peningkatan Kebijakan Lingkungan - Dewi Arinda Putri; Fahim Kusuma Wardani; Adelia Dyah Ayu Maharani; Nunun Nurhajati (STISIP Margarana, 2026)
The development of drainage channels is one of the ways local governments implement policies to address flooding and improve urban environmental quality. This study aims to evaluate the implementation of the drainage development program on Teungku Umar Street, Tulungagung Regency, using the policy implementation theory proposed by George C. Edward III, which focuses on four elements: communication, resources, implementers’ disposition, and bureaucratic structure. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants involved include local government officials, project implementers, village administrative staff, and local residents. The findings indicate that the drainage development has produced initial positive impacts, particularly improvements in the physical condition of drainage channels and a reduction in water stagnation. However, the effectiveness of policy implementation remains suboptimal due to several constraints, including non-continuous communication, limited resources—especially in terms of budget and supervision—an implementation approach that prioritizes physical project completion, and insufficient inter-bureaucratic coordination. Therefore, enhanced communication, strengthened resources, sustained commitment from implementers, and improved inter-agency coordination are required to ensure that flood control objectives and environmental policy goals can be achieved effectively and sustainably.